Role of Inflammatory Cell Responses in Stimulating Fibroblasts in Diabetic Oral Ulcer after Treatment with Liquid Smoke of Coconut Endocarp: A Histological Assessment - Ernawati, Diah Savitri; Surboyo, Meircurius Dwi Condro; Ayuningtyas, Nurina Febriyanti; Nagoro, Ayu Anggraini Broto (European Journal of Dentistry, 2020)
Objective The liquid smoke of coconut endocarp (LS-CE) contains high antioxidants that promote oral ulcer healing in diabetics. This study reveals the profile of inflammatory cell responses to oral ulcer healing in diabetics under treatment with LS-CE.Materials and Methods A diabetic model was induced with alloxan. Treatment with LS-CE was performed on oral ulcer at a dose of 1 μL/g weight for 3, 5, and 7 days. The anti-inflammatory effect was tested on animal’s oral ulcer model by measuring the inflammatory cell responses of the neutrophils, macrophages, lymphocytes, and fibroblasts through histological assessment.Results The LS-CE stimulated the healing by simultaneously increasing the inflammatory cell responses. The numbers of neutrophils, macrophages, and fibroblasts after treatment for 7 days are higher than that after 3 days and 5 days (p < 0.01), but not for neutrophils. The LS-CE shows increase in the fibroblasts by hastening responses of macrophage recruitment by five times, but not neutrophil and lymphocyte recruitment. The higher phenolic compounds in LS-CE are responsible for increase in the proliferation of fibroblasts, as it hastens cellular responses of macrophages.Conclusions The application of LS-CE enables hastening of the healing of diabetic oral ulcer by stimulating the macrophages.
Keywords: liquid smoke; coconut endocarp; inflammatory; oral ulcer; macrophages; fibroblast